TEKOHÁ: A Virtual Reality Game for Teaching the History of the Jesuit Missions in Rio Grande do Sul - Martirns Junior, Renato V.; Souza, Vinicius C.; Oliveira, Kleinner S. F.; Ponzoni, Gabriel; Birck, Johnny F.; Machado, Daniel M.; Flores, Igor (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2025: Anais do XXIV Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames.2025.10337, 2025)
Introduction: Virtual Reality (VR) is a computational technology that has grown in many ways, being increasingly used in different contexts. Numerous studies on the use of VR in adult education have shown positive results, however, little is known about the use of VR in children’s education. Objective: this work has the aim to develop a virtual reality game to teach the history of the Jesuit Missions in Rio Grande do Sul to elementary school children. Steps: workshop with elementary school teachers, virtual reality game design and VR game development. Results: a VR game that can be used in schools to support the teaching and learning process of the history of the Jesuit Missions in RS, allowing children to visit São Miguel das Missões without having to leave school.